Thermal behavior of the Cu-10 mass%Al and Cu-10 mass%Al-4 mass%Ag alloys - Adorno, A. T.; Silva, RAG (Kluwer Academic Publ, 2004)
The thermal behavior of the Cu-10 mass%Al and Cu-10 mass% Al-4 mass%Ag alloys was studied using classical differential thermal analysis (DTA), optical microscopy (OM) and X-ray diffractometry (XRD). The DTA curves were obtained for annealed and quenched samples. The results indicated that the presence of silver introduces new thermal events, associated to the formation of a silver-rich phase, to the shift of the equilibrium concentration to higher A1 contents and to the decomposition of the silver-rich phase in the same temperature range of the beta(1) phase decomposition.
Keywords: Cu-Al and Cu-Al-Ag alloys; phase transformation; thermal behavior